Carbon material‐based anodes in the microbial fuel cells - Xiaoqi Fan; Yun Zhou; Xueke Jin; Rong‐Bin Song; Zhaohui Li; Qichun Zhang (Carbon Energy, 2021)
Abstract For the performance improvement of microbial fuel cells (MFCs), the anode becomes a breakthrough point due to its influence on bacterial attachment and extracellular electron transfer (EET). On other level, carbon materials possess the following features: low cost, rich natural abundance, good thermal and chemical stability, as well as tunable surface properties and spatial structure. Therefore, the development of carbon materials and carbon‐based composites has flourished in the anode of MFCs during the past years. In this review, the major carbon materials used to decorate MFC anodes have been systematically summarized, based on the differences in composition and structure. Moreover, we have also outlined the carbon material‐based hybrid biofilms and carbon material‐modified exoelectrogens in MFCs, along with the discussion of known strategies and mechanisms to enhance the bacteria‐hosting capabilities of carbon material‐based anodes, EET efficiencies, and MFC performances. Finally, the main challenges coupled with some exploratory proposals are also expounded for providing some guidance on the future development of carbon material‐based anodes in MFCs.